Detection of thyroid cancer by an FDG-PET cancer screening program: a Japanese nation-wide survey - Minamimoto, Ryogo; Senda, Michio; Jinnouchi, Seishi; Terauchi, Takashi; Yoshida, Tsuyoshi; Inoue, Tomio (Anticancer research, 2014)
The [(18)F]-fluorodeoxyglucose positron emission tomography (FDG-PET) cancer screening program is defined as a cancer screening for asymptomatic subjects using FDG-PET (including PET/ computed tomography [CT]) with or without combination of other screening tests. The aim of the present study was to analyze the thyroid cancer detection rate in asymptomatic individuals through a FDG-PET cancer screening program in Japan. A total of 153,775 asymptomatic individuals underwent FDG-PET cancer screening. We analyzed 1,308 cases for possible thyroid cancer in all screening tests. Among the 1,308 possible cases, 353 were verified as thyroid cancer. The relative sensitivity and positive predictive value (PPV) of FDG-PET were 90.7% and 29.5% for thyroid cancer, respectively. The relative sensitivity was equivalent to thyroid ultrasonography (US) (90.9%) and higher than neck computed tomography (CT) (75.7%, p<0.001), thyroglobulin (36.1%, p<0.001), and carcinoembryonic antigen (5.6%, p<0.001). The sensitivity with a PET/CT scanner was higher than that with a dedicated PET scanner (94.1% vs. 85.0%, p<0.001). Combining thyroid US with FDG-PET increased the relative sensitivity and PPV. The majority of thyroid carcinomas detected by FDG-PET screening were Union for International Cancer Control (UICC) stage I, but a significant number of cases were also detected as stage III or IV. The FDG-PET cancer screening program in Japan detected thyroid cancer at an early stage. FDG-PET showed high sensitivity in detecting thyroid cancer, and it may be more effective if combined with thyroid US.